ʻAre we still good Europeans?ʼ Jürgen Habermas and the Italian crisis - Lombardinilo, Andrea (Italian Sociological Review, 2020)
This essay focuses on recent Habermas’s reflection upon the ʻItalian crisisʼ, with the aim to investigate the connection between his recent essayistic production on the crisis of European Union and the speech delivered in Berlin on July 4, 2018, when he was awarded the German-French Journalist Prize. He shed light on the ʻItalian crisisʼ and European incapability to realize the specific needs of the poorer member states, which risk being overwhelmed by old and new populisms fired by anti-migrant and anti-liberal rhetoric. Habermas’s speech, entitled Are we still good Europeans?, can be interpreted as a sample of ʻquality pressʼ, useful to build a coherent public sphere founded on ʻconsidered public opinionsʼ. Thus, Habermas’s journalistic insights allow us to update his assertions about the future of the European Union which he already focused on in Europe: The Faltering Project (2008), The Crisis of the European Union (2011) and The Lure of Technocracy (2013). The Italian political crisis is also a communicative affair, as Habermas points out criticizing German stubbornness in approving economic austerity, thus neglecting the looming risks of incommunicability between national and supra-national governances.